Infection of Ophiocordyceps sinensis Fungus Causes Dramatic Changes in the Microbiota of Its Thitarodes Host - Wu, Hua; Rao, Zhong-Chen; Cao, Li; De Clercq, Patrick; Han, Ri-Chou (Frontiers in Microbiology, 2020)
The Chinese cordyceps is a unique and valuable parasitic complex of Thitarodes/Hepialus ghost moths and the Ophiocordyceps sinensis fungus for medicine and health foods from the Tibetan Plateau. During artificial cultivation of Chinese cordyceps, the induction of blastospores into hyphae is a prerequisite for mummification of the infected Thitarodes larvae. To explore the microbiological involvement in the induction of mycelia-blastospore transition, the microbiota of the hemolymph and gut from Thitarodes xiaojinensis larvae with or without injected O. sinensis blastospores were investigated by culture-dependent and -independent methods. 25 culturable bacterial species and 14 fungal species, together with 537 bacterial OTUs and 218 fungal OTUs, were identified from the hemolymph and gut of samples from five stages including living larvae without injected fungi (A) or with high blastospore load (B), mummifying larvae without mycelia coating (C), freshly mummifying larvae coated with mycelia (D), and completely mummified larvae with mycelia (E). Two culturable bacterial species (Serratia plymuthica, Serratia proteamaculans), and 47 bacterial and 15 fungal OTUs were considered as core species. The uninfected larval hemolymph contained 13 culturable bacterial species but no fungal species, together with 164 bacterial and 73 fungal OTUs. To our knowledge, this is the first study to detect large bacterial communities from the hemolymph of healthy insect larvae. When the living larvae contained high blastospore load, the culturable bacterial community was sharply inhibited in the hemolymph but the bacterial and fungal community greatly increased in the gut. In general, high blastospore load increased bacterial diversity but sharply decreased fungal diversity in the hemolymph and gut by OTUs. The bacterial loads of four culturable species (Chryseobacterium sp., Pseudomonas fragi, S. plymuthica, S. proteamaculans) increased significantly and O. sinensis and Pseudomonas spp. became dominant microbes, when the infected larvae became mummified, indicating their possible involvement in the larval mummification process. The discovery of many opportunistic pathogenic bacteria in the hemolymph of the healthy larvae, the larval microbial diversity influenced by O. sinensis challenge and the involvement of dominant bacteria during larval mummification process provide new insight into the infection and mummification mechanisms of O. sinensis in its Thitarodes hosts.